On New Properties of Graphs with Magic Type Labeling - Semeniuta, M.F.; Sherman, Z.O. (Управляющие системы и машины, 2019)
We have shown the connection between vertex labelings of magic graph and its overgraph. Also, we have introduced binary relation on the set of all -distance magic graphs, where , i=1, 2, … and proved, that it is equivalence relation. Therefore, we have explored the properties of the graphs, which are in this relation. Finally, we have offered the algorithm of constructing r-regular handicap graph of order n, where n ≡ 0(mod8), r ≡ 1,3(mod4) and 3 ≤ r ≤n–5.